Association of single nucleotide polymorhism in microrna 196a2 and 146a gene towards risk for lung cancer in north Indian population - Arora, Inderjot Kaur (My University, 2013)
MicroRNAs (miRNAs) are small RNA molecules that regulate the expression of corresponding messenger RNAs (mRNAs). Variations in the level of expression of distinct miRNAs have been observed in the genesis, progression and prognosis of multiple human malignancies. The present study was aimed to investigate the association between two highly studied miRNA polymorphisms (mir-146a rs2910164, mir-196a2 rs11614913) and cancer risk. A case-control study was performed on North Indian population. Odds ratio (OR) and 95% confidence interval (95% CI) were used to investigate the strength of the association. Participants who possessed CC (mutant type) genotypes for miRNA 146a gene showed high risk for lung cancer (OR=5.648, 95%C.I; 0.64-49.8, p=0.08) especially for SQCC and SCLC compared to those who possessed GC or GG genotypes. The association also persisted among non-smokers. On the other hand TT (mutant genotype for miRNA 196 a2 gene also showed high risk for lung cancer (OR=3.78, 95%C.I; 0.94-15.2, p=0.04) especially SCLC and ADCC. Smokers with mutant genotype were more susceptible for lung cancer risk as compared to nonsmokers. Individuals having combined mutant or variant genotype for both the genes (OR=3.8, 95%C.I; 1.2-12.1 and p=0.02) were at much higher risk for lung cancer as compared to those having single nucleotide polymorphism for either of the two genes. The present study suggests an important role of mir-196a2 rs11614913 and rs291014 polymorphism with overall lung cancer risk especially in North Indian population. Further studies with large sample size are needed to evaluate and confirm this association.
Master of Science-Biotechnology
Keywords: lung cancer miRNA; SNP; North Indian Population